PEMUTUSAN HUBUNGAN KERJA KARENA PELANGGARAN BERSIFAT MENDESAK PASKA UNDANG-UNDANG CIPTA KERJA: PERSPEKTIF CRITICAL LEGAL STUDY - Miaz, Hasnuldi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
: This research aims to explain Article 52 paragraph 2 PP 35/2021 which regulates the reasons for Termination of Employment (PHK) due to urgent violations. This model of layoff provides compensation in the form of compensation and separation pay. Furthermore, Article 52 paragraph 3 PP 35/2021 states that employers can do this without a layoff notification letter. Thus, the assumption is that the process begins with bipartite negotiations, mediation, and the Industrial Relations Court/Supreme Court. This allegation is based on the application of the law so far and the provisions of Article 39 paragraph 2 and paragraph 3 of PP 35/2021. It requires bipartite negotiations between employers and workers if workers reject the layoff notification, then proceed according to the industrial relations dispute resolution mechanism. However, in practice, the application of this article varies, even in the context of its interpretation. This raises crucial issues, including: (1) how will layoffs be regulated due to urgent violations after the Job Creation Law? (2) How are layoffs due to violations pressing from a critical legal study perspective? To uncover these legal problems, normative research is used through philosophical, statutory and conceptual approaches. The results of this research conclude that the practice of implementing layoffs due to urgent violations often causes blunders. When workers refuse layoffs, employers ultimately have to return to the industrial relations dispute resolution mechanism. The author hopes that the Supreme Court will be willing to provide guidance on implementing layoffs due to urgent violations. Especially regarding the legality of unilateral layoffs carried out by the Company. There are at least two problems. First, regarding the time of termination of the employment relationship, whether following the Company's layoff letter or calculated from the time the PHI decision was read. Second, regarding compensation, whether an urgent violation can be qualified as a PP/PKB violation with compensation under Article 52 paragraph 1 PP 35/2021 considering the principle of presumption of innocence or whether it remains with the compensation amount regulated by Article 52 paragraph 2